Analysis of Laser Hardening Possibility of Teeth of Loaded Cylindrical Gears Made of Structural Steels - Mark M. Kane; Oleg G. Devoino; Irina V. Shvets (Механика машин, механизмов и материалов)
The relevance is shown for replacing expensive alloy steels, of which loaded cylindrical gears are currently made, with cheaper (up to 2.5 times) structural steels, improving the processes of hardening the teeth of loaded cylindrical gears and reducing their cost. The disadvantages of the most common methods of hardening loaded gears are presented. The possibilities of modern methods of surface hardening of metals using laser radiation are described. The main results of studying the influence of the conditions of laser hardening of 40Х (40Kh) structural steel samples by a scanning laser beam on the hardness and roughness of the sample surfaces are given. For typical operating conditions of cylindrical gears of automotive transmissions, a calculated assessment was performed for the possibility of providing the required transmission life when using 40Kh structural steel for the manufacture of gears with subsequent hardening of the teeth with a scanning laser beam.